Pengaruh Kualitas Pelayanan Dan Penanganan Keluhan Terhadap Pembiayaan Bermasalah Di BMT Artha Abadi - Ika Wahyu Purnama; Miswan Ansori; Mubarok, Ahmad Fauzan (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
This research aims to analyze the influence of service quality and complaint handling on problematic financing at BMT Artha Abadi Jepara. The method used in this research is a quantitative method with a field research design. The research sample was 32 respondents. The data analysis used is multiple linear regression analysis with the help of SmartPLS4 software. The research results show that service quality has no effect on financing problems at BMT Artha Abadi Jepara (p-value: 0.384>0.05). Handling complaints has no effect on problematic financing at BMT Artha Abadi Jepara (p-value: 0.215>0.05). Service quality and complaint handling simultaneously or together influence problematic financing at BMT Artha Abadi Jepara (p-value: 0.000<0.05). The results of this research can be an alternative solution to reduce the high number of financing problems that often occur in various financial institutions. Through this research, it was found that jointly or simultaneously, service quality and complaint handling can influence problematic financing. In this way, it is hoped that it can make a contribution to financial institutions experiencing problems related to problematic financing.